Effect of Height and Type of Nursery Shade on Vigor of Big Red Chili (Capsicum Annum L.) - Imam Wahyudi; Muhammad Abror (Nabatia, 2014)
Aim of this experiment was to study the effect of highness and type of shade material within interaction between highness and types of shade material nurserytowards big red chili vigor (C. annum L.). This research was conducted on February-March 2012 district Turirejo, Cangkringmalang, Beji, Pasuruan denan with the highness of 9 m dpl, pH 5-6, temperature at 30oC, rainfall 420 mL/tahun. This research was design by factorial in Randomized Block Design (RBD), which were run triplicate. The first factor were shade 65, 95 dan 125 cm and the second factor were the type of plastic nursery shade material, paranet and (plastic + paranet). The data showed that was interaction between highness and types of shade material nurseryon parameter of highness, cotyledons emergence time, length of leaf, amount of leaf, diameter rod, the number of nodes grows and plant fresh weight. The combined height 65cm shade and shade types of materials (plastics + paranet) was the best treatment while it was not significantly different to the other treatments.